1985
DOI: 10.1002/ana.410180113
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and herpes simplex virus ascending myelitis in a patient with acquired immune deficiency syndrome

Abstract: Progressive ascending myelitis was the presenting feature of the acquired immune deficiency syndrome (AIDS) in a homosexual man who also had Kaposi's sarcoma, Pneumocystis pneumonia, and disseminated cytomegalovirus (CMV) infection. Neuropathological studies showed profuse cytomegalic cells throughout the brain and spinal cord, but no inflammatory response. At postmortem examination, CMV and herpes simplex virus, type 2 (HSV-2), were recovered from multiple sites throughout the central nervous system (CNS). HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
4

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(35 citation statements)
references
References 26 publications
2
29
0
4
Order By: Relevance
“…In previous reports, HSV myelitis was accompanied by conditions that reduce immunologic competence, such as acquired immunodeficiency syndrome [5,6], malignancies [7,8], and diabetes mellitus [3]. Ellie et al [12] and Flope et al [13] have recently reported HSV myelitis in nonimmunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, HSV myelitis was accompanied by conditions that reduce immunologic competence, such as acquired immunodeficiency syndrome [5,6], malignancies [7,8], and diabetes mellitus [3]. Ellie et al [12] and Flope et al [13] have recently reported HSV myelitis in nonimmunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other severe neurological complications such as encephalitis, meningitis and lethal panmyelitis, have been described, especially in the immunocompromised host [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Since either CMV or HSV-2 can infect multiple cell types (neurons, astrocytes, oligodendrocytes and microglia) in the CNS 3,12 we can speculate on a possible synergistic effect of this concurrent infection in producing spinal cord lesion. To corroborate this hypothesis, we were able to find only three previous reports 8,17,23 in HIV patients. All these patients had profound immunosuppression, and the prognosis was grim in the two patients it was available (death in one and minimal recovery in the other).…”
Section: Discussionmentioning
confidence: 61%